ANALYSIS OF PURCHASE ACCOUNTING INFORMATION SYSTEM BY USING THE COBIT FRAMEWORK 4.1 AT PT. TELEKOMUNIKASI INDONESIA, TBK BANDUNG - Sagala, Sri Widianingsih Rauli; Purba, Heddry (11th International Scholars Conference, 2016)
This research was conducted to find out the performance of purchase accounting information system by used domain Monitor and Evaluate, which assessed by Maturity Level in COBIT 4.1 Framework, where the purchase accounting information systems play an important role in purchasing activity in the company. The method undertaken in this research was descriptive qualitative method, where data obtained through interviews, questionnaires and documentation, and then interpreted to be able to give a conclusion. And uses descriptive qualitative data analysis techniques which aims to provide an overview and research on the performance of the purchase accounting information system at PT. Telkom Indonesia, Tbk Bandung. Based on the results of the research, an analysis of the accounting information system of sales by using Monitor and Evaluate domain was at the level of 4.15, which was obtained from the average of four existing sub domains on Monitor and Evaluate domain, namely: ME1 Monitor and Evaluate IT Performance was at the level of 4.12, ME2 Monitor and Evaluate Internal Control was at the level of 4.50, ME3 Ensure Compliance with External Requirements was at the level of 3.67, and ME4 Provide IT Governance was at the level of 4.33. The meaning of number 4.15 was that the purchase accounting information systems at the level of 4 or Managed, which means that the company has so far satisfied with the existing system, information generated faster, relevant, reliable, and actual. Improving the quality and speed of information is directly proportional to the decision- making by management. Thus these IT-based SI has the competitive advantage both in multinational companies or competitors engaged in the same type of industry, namely telecommunications.